Efl Teacher Trainees’ Engagement and Prespectives in Reading Activities Through Literature Circle: A Narrative Study - Mulyana, Restu Putra; Iskhak, Iskhak; Friatin, Lilies Youlia (Universitas Galuh, 2025)
In the realm of English as a Foreign Language (EFL) education, developing effective reading skills among trainee teachers is a critical challenge. This research aims to explore the views and efficacy of the Literature Circle method as a pedagogical tool to increase engagement and proficiency levels among EFL teachers during their reading activities. The researcher took two participants as samples for interviews. Qualitative research methodology, specifically a narrative study design, was used to explore participants' perspectives and involvement in reading activities through literature circles in the context of EFL teaching. Data were collected primarily through semi-structured interviews, using content analysis. Research findings show that literature circles have a significant positive influence on engagement, comprehension of texts, and development of social and critical thinking skills of prospective English teachers. Thus, it can be implied that literature circles are a transformative educational tool for trainee teachers, cultivating critical skills, empathy, and collaborative learning. This research has implications for teaching institutions in Indonesia and it is believed that its implementation will further encourage students' interest in reading.